2005
DOI: 10.1210/en.2004-1603
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Lard, But Not Total Lard Calories, Damps Adrenocorticotropin Responses to Restraint

Abstract: Although rats given the choice of eating high-density calories as concentrated sucrose solutions or lard exhibit reduced responsivity in the hypothalamo-pituitary-adrenal axis, rats fed high-fat diets have normal or augmented responses to stressors. To resolve this apparent discrepancy, we compared in adult male rats the effects of 7-d feeding with lard + chow (choice) to feeding a 50% lard-chow mixture (no-choice) and to chow only. Rats with choice composed diets with 50-60% total calories from lard. Rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 57 publications
4
104
4
2
Order By: Relevance
“…Anorexia induced by acute and repeated restraint stress was followed by increased proportion of comfort food eating (with high fat/sugar contents) (Dallman, 2010;Dallman et al, 2005;Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004). In contrast to normal diet, when sweet food was presented to the stressed animals repeated mild pinch resulted in hyperphagia and considerable gain in body weight (Rowland and Antelman, 1976) (Table 1).…”
Section: Stress-induced Comfort Food Eatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Anorexia induced by acute and repeated restraint stress was followed by increased proportion of comfort food eating (with high fat/sugar contents) (Dallman, 2010;Dallman et al, 2005;Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004). In contrast to normal diet, when sweet food was presented to the stressed animals repeated mild pinch resulted in hyperphagia and considerable gain in body weight (Rowland and Antelman, 1976) (Table 1).…”
Section: Stress-induced Comfort Food Eatingmentioning
confidence: 99%
“…Food intake Anorexia (Bazhan et al, 2007;De Souza et al, 2000;Fryer et al, 1997;Harris et al, 2001;Krahn et al, 1990;Rybkin et al, 1997) Hyperphagia (Dallman, 2010;Dallman et al, 2005;Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004) Mechanisms Stress induces anorexia due to decreased signaling of: AgRP (Chagra et al, 2011;Kas et al, 2005) NPY (Tempel and Leibowitz, 1994;White, 1993) due to increased signaling of: insulin? (Chavez et al, 1997;Warne, 2009) leptin?…”
Section: Q4mentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting reports about the stress responsiveness of rats maintained on HF diet [65][66][67][68] and the differences may be accounted for by the variety of animal models and stress paradigms used. HF animals in our pilot study had an enhanced corticosterone response to 1-hour restraint stress prior to colony formation, but they subsequently had typical behavioral responses to VBS.…”
Section: High Fat Diet In the Vbsmentioning
confidence: 99%
“…It may be possible that SUB behavior will change if they are presented with diets composed of different macronutrients to consume, such as a high fat (HF) diet, or if they are provided with a choice of macronutrients. It has been suggested that having a choice of which macronutrient to consume can play a significant role in macronutrient influences on the negative effects of stress [68]. These are interesting considerations that warrants future study.…”
Section: High Fat Diet In the Vbsmentioning
confidence: 99%